Gestão acadêmica: a percepção da comunidade de um mestrado profissional da Universidade Federal da Paraíba - França, Junielle Menezes (2022)
Academic management is understood as the practice of pedagogical and administrative procedures aimed at monitoring and guiding the student. The main objective of this research is to analyze the perception of students, professors and administrative technicians in relation to the academic management of the secretariat of the Postgraduate Program in Management in Learning Organizations - PPGOA, specifically aiming to verify the main academic management procedures carried out by this sector; to identify the strengths and weaknesses related to the academic management of the PPGOA and to prepare a guiding document for routines and procedures of academic management practices carried out by the program secretariat. As for the methodology, this study is descriptive, with a qualitative approach, using as a data collection technique three online questionnaires, with specific questions for each group, objective and subjective inquiries, which were carried out with students, teachers and the technical staff. administration of the PPGOA. The data obtained in this research were worked through the method of document analysis and (Bardin, 2013) content analysis. In addition, some data, from objective questions, were analyzed using the Excel program and worked in the form of tables to facilitate the visualization of the data. In the results, it is highlighted that the perception of 55.1% of the research participants in relation to the academic management of the PPGOA secretariat is considered satisfactory. rules governing the program. As for the weaknesses identified by the respondents, some were more mentioned, such as difficulty in communicating with the program secretariat, limitations regarding updating the PPGOA website and servers with work overload. Regarding the potential, the main one highlighted by the participants was the service provided by the administrative technicians of the PPGOA, being considered fast, efficient, provided by trained professionals. Therefore, this research made it possible to verify how relevant it is to have a guiding material containing the norms, routines and procedures of this sector, since this document, in addition to guiding people who use the services of the secretariat, will also inform the society that it wants to know and to which needs the services of the program, as is the operation of PPGOA.